PENERAPAN PRINSIP LOCUS DELICTI DALAM PENYIDIKAN TINDAK PIDANA DI WILAYAH PERAIRAN (Studi Pada Direktorat Kepolisian Perairan Kepolisian Daerah Sumbar) - Chandra, Renol (UNES Law Review, 2019)
Article 73 of Law Number 45 of 2009 concerning Fisheries regulates the authority to investigate criminal acts in territorial waters by Aquatic Police Investigators. In the territorial waters there are so many criminal acts that occur where the crime scene (locus delicti) is in the territorial waters. To determine the place of occurrence of a crime is not easy, but determining the location of a crime case plays an important role for various problems in the criminal procedural law, namely concerning the interests of investigation and the relative competence of the court that will examine the case, as faced by Ditpolair Polda Sumbar in investigating fisheries